Attitudes and Motivations Graduates in Digital Entrepreneurship - Natrah, Lutfiah (Online Journal for TVET Practitioners, 2022)
The adoption of technology in entrepreneurship makes technical graduates easier to involve in business.  Hence, this study is to identify the perception of attitudes and motivation of students towards digital entrepreneurship, as well how these differs in gender and academics’ background. This quantitative study consisted sample of 331 final year students from various faculties in the Malaysian University. Questionnaires were distributed via online. The study’s findings revealed that study found that the perception of attitude and motivation towards digital entrepreneurship among students is high. It also found that the perception of attitudes and motivation of female students higher than male. In conclusion, the study’s finding led to important implementation implication for entrepreneurship activities in campus based on the gender.